The Marcus Garvey and Universal Negro Improvement Association Papers. - Bair, Barbara; Ball, Tevvy; Blum, Erika A.; Hill, Robert A.; Hughes, Arnold; Kao, Chin C.; Rasmussen, R. Kent (The Marcus Garvey and Universal Negro Improvement Association Papers, 1995)
"Africa for the Africans" was the name given in Africa to the extraordinary black social protest movement led by Jamaican Marcus Mosiah Garvey (1887-1940). Volumes I-VII of the Marcus Garvey and Universal Negro Improvement Association Papers chronicled the Garvey movement that flourished in the United States during the 1920s. Now, the long-awaited African volumes of this edition (Volumes VIII and IX and a forthcoming Volume X) demonstrate clearly the central role Africans played in the development of the Garvey phenomenon. The African volumes provide the first authoritative account of how Africans transformed Garveyism from an external stimulus into an African social movement. They also represent the most extensive collection of documents ever gathered on the early African nationalism of the inter-war period. Here is a detailed chronicle of the spread of Garvey's call for African redemption throughout Africa and the repressive colonial responses it engendered. Volume VIII begins in 1917 with the little-known story of the Pan-African commercial schemes that preceded Garveyism and charts the early African reactions to the UNIA. Volume IX continues the story, documenting the establishment of UNIA chapters throughout Africa and presenting new evidence linking Garveyism and nascent Namibian nationalism.